ANALISA MENGURAS MENUTUP DAN MENGUBUR DUSUN BRANJANGAN TIJAYAN MANISRENGGGO KLATEN - Wulandari, Dewi Ariyani (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT Still there are 41 villages which became endemic DHF areas . The number of cases highest in Klaten Regency DHF occurred in the hamlet of Branjangan. DHF is happening in the district. Due to the lack of a level of knowledge and awareness in the role as well as to keep the environment clean. This research is to know the relation of knowledge and behavior of drain close and bury (3M) plus on a head of household with the incidence of dengue in the hamlet Branjangan, Tijayan, Manisrenggo Klaten. This type of analytical observational research with cross sectional approach. This research population as much as 122 heads of families by the number of samples of 55 people. Data sheet measured by check. Data analysis using the chi square p=0.05 level. Chi square correlation test results knowledge with DHF of 0.030 and behavior 3M plus with DHF of 0.016. Level of knowledge of the head of the family on the category either as many as 61.8%, quite as 20%, and less as 18.2%. The behavior of the head of the family about 3M plus on either category as much as 23.6%, quite as 27.3%, and less as 49.1%. No association with the incidence of dengue the knowledge and the are behavioral relationships 3M plus with incidence of dengue in hamlet Branjangan, Tijayan Manisrenggo, Klaten. Keywords: Knowledge; kehavioral; 3M Plus; genesis DHF